Indonesia FAKTOR YANG MEMPENGARUHI ANEMIA PADA REMAJA PUTRI DI SMP 2 KABPATEN ROKAN HULU : Indonesia - Desri Yulda; Rifa Yanti (Jurnal Ilmu Kebidanan, 2022)
Young women are ten times more likely to suffer from anemia than young men. Lack of Hb levels in the blood will have an impact on fatigue and stress on the body's organs. Loss of iron intake and no absorption and formation of red blood cells that often occur at puberty. This study aims to determine the determinants associated with the incidence of anemia in young women in SMP 2 Kabun, Rokan Hulu Regency. The sample in this study were 7th and 8th grade students of SMP 2 Kabun, Rokan Hulu Regency, Rokan Hulu Regency, as many as 92 people with total sampling techniques and the chi square test statistical analysis. The result showed that there was a significant relationship between knowledge (p value = 0.001), menstrual patterns (p value = 0,000) and eating patterns (p value = 0.038) with the incidence of anemia in adolescent girls in SMP 2 Kabun . Researchers suggest to young women to always consume blood-added tablets (TTD) and iron-rich foods to prevent iron nutrient anemia.